2024
DOI: 10.1186/s12870-024-04770-w
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical and growth-associated traits of basil (Ocimum basilicum L.) affected by silver nanoparticles and silver

Shahla Hashemi Shahraki,
Tayebeh Ahmadi,
Babak Jamali
et al.

Abstract: Background The biochemical and growth changes resulting from exposure of basil (Ocimum basilicum L.) seedlings to silver nanoparticles and silver were investigated. Over a two-week period, seedlings were exposed to different concentrations (0, 40, and 80 ppm) of silver nanoparticles and silver. Results Our findings revealed that at concentrations of 40 and 80 ppm, both silver nanoparticles and silver nitrate led to decreased weight, root and shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Several studies suggest that the harmful effects of silver nanoparticles on plants may be caused by: (i) excessive production of ROS by redox cycling; (ii) size dependent mechanical damage of nanoparticles (Jiravova et al 2016 ; Amooaghaie et al 2018 ); (iii) oxidation of silver nanoparticles and produced silver ions (Shahraki et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that the harmful effects of silver nanoparticles on plants may be caused by: (i) excessive production of ROS by redox cycling; (ii) size dependent mechanical damage of nanoparticles (Jiravova et al 2016 ; Amooaghaie et al 2018 ); (iii) oxidation of silver nanoparticles and produced silver ions (Shahraki et al 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…The purchased silver nanoparticles, utilized in powder form, had an average reported size of 20 nanometers according to the manufacturer’s information (US Research Nanomaterial, Inc., 3302 Twig Leaf Lane, Houston, TX 77,084, USA). The size of nanoparticles was confirmed by scanning electron microscope (Model JSM 6390LV, JOEL, USA) and showed that the nanoparticles were homogeneous (Shahraki et al 2024 ). Following this experimental phase, the plants were harvested for further evaluation.…”
Section: Methodsmentioning
confidence: 99%